Analisis Kesejahteraan Petani: Pola Penguasaan Lahan Di Kabupaten Lamongan (Jurnal Ekonomi dan Kebijakan Pembangunan, 2018)
Pattern of landholding affects effectiveness of the agricultural sector. This study aims to identify the determinants of landholding. The objectives are to identify the determinants of wet land and dry land held by farm household in Lamongan Regency and to calculate Gini coefficient of agricultural land in Lamongan Regency. Data was obtained from Agricultural Census 2013. Specifically, this study utilizes household cross sectional data with 189   343 observations. This research utilizes multiple regression analysis. The results show that age, gender of head of household, household size, main source of income, and dummy for asset are significantly influencing wet landholding, while factors insignificantly affecting dry landholding is gender of head of household and age. Regarding wet land as asset accumulation for farm household, the results show that farmers experience a decreasing marginal accumulation on wet landholding. The Gini coefficient of agricultural land in Lamongan Regency is 0.49 and it shows that Lamongan Regency experiences moderate inequality in term of land holding.